Probiotics, prebiotics, and postbiotics in health and disease - Jing Ji; Weilin Jin; Shuang‐Jiang Liu; Zuoyi Jiao; Xiangkai Li (MedComm, 2023)
Abstract The gut microbiota and its homeostasis play a crucial role in human health. However, for some diseases related to the gut microbiota, current traditional medicines can only relieve symptoms, and it is difficult to solve the root causes or even cause side effects like disturbances in the gut microbiota. Increasing clinical studies and evidences have demonstrated that probiotics, prebiotics, and postbiotics can prevent and treat various diseases, but currently they can only be used as dietary supplements rather than medicines, which restricts the application of probiotics in the field of medicine. Here, this review analyzes the importance of gut microbiota in human health and the current problems of traditional medicines, and systematically summarizes the effectiveness and mechanisms of probiotics, prebiotics, and postbiotics in maintaining health and treating diseases based on animal models and clinical trials. And based on current research outcomes and development trends in this field, the challenges and prospects of their clinical application in maintaining health, alleviating and treating diseases are analyzed. It is hoped to promote the application of probiotics, prebiotics, and postbiotics in disease treatment and open up new frontiers in probiotic research.